To convert the quadratic from vertex form to standard form, we start with the given vertex form of the quadratic:
\[ y = 2(x - 5)^2 - 10 \]
Now, we will expand and simplify this expression step by step.
- First, expand the squared term:
\[ (x - 5)^2 = x^2 - 10x + 25 \]
- Substitute this back into the equation:
\[ y = 2(x^2 - 10x + 25) - 10 \]
- Distribute the 2:
\[ y = 2x^2 - 20x + 50 - 10 \]
- Combine like terms:
\[ y = 2x^2 - 20x + 40 \]
Now, we have the quadratic in standard form \( y = ax^2 + bx + c \), where \( a = 2 \), \( b = -20 \), and \( c = 40 \).
Thus, the standard form of the quadratic is:
\[ y = 2x^2 - 20x + 40 \]